Exogenous citric acid, salicylic acid, and putrescine treatments preserve the postharvest quality and physicochemical properties of broccoli (Brassica oleracea L. var. italica) during cold storage - Kibar, Hakan; Kibar, Beyhan; Turfan, Nezahat (Wiley, 2023)
AbstractTo extend the postharvest storage life of broccoli samples (Brassica oleracea L. var. italica), an exogenous application of citric acid (CA), salicylic acid (SA), and putrescine (PUT) was tested in multiple combinations (0.5 and 1 mM) at 4 ± 0.5°C and 90 ± 5% relative humidity (RH) for 21 days (d). The weight loss (WL), respiration rate (RR), total soluble solids (TSS), pH, color (L*, a*, b*, chroma, and hue angle), proximate and mineral contents, phenolic and flavonoid contents, and other biochemical properties of the treated and untreated broccoli samples were evaluated throughout the storage duration. The lowest WL was observed when exposed to 0.5 mM of PUT. 1 mM CA and PUT treatments were affected by RR, depending on storage conditions. The lowest TSS content was observed in broccoli samples treated with 0.5 mM CA among all treatments. The chroma value of the samples was preserved by the 0.5 mM SA treatment. The most abundant element in broccoli samples was potassium in the control application, followed by a 1 mM SA treatment. In addition, the protein content was the highest in the 1 mM PUT treatment. The highest vitamin C was determined in the 1 mM CA treatment, and the most abundant vanillic acid was found in broccoli exposed to the 0.5 mM and treatment. Glucose content was determined at the lowest level in the 0.5 mM SA treatment, while higher increases occurred in other treatments. In terms of these findings, 1 mM CA, 1 mM SA, and 1 mM PUT delay WL, RR, and color degradation and prolong the storage life of broccoli samples stored at 4 ± 0.5°C. It was concluded that the biochemical content, fresh weight, and green color of broccoli samples throughout postharvest and storage can be maintained longer by exogenous application of these natural compounds. Therefore, we recommend 1 mM PUT and 1 mM CA treatments to maintain the quality of broccoli by minimizing losses in morphological properties, mineral, and biochemical compositions during postharvest storage.
Keywords: Color Properties; Shelf-Life; color properties; broccoli sample; flavonoid; mineral composition; phenolic; Flavonoid; Antioxidant Activity; Health-Promoting Compounds; Original Articles; Broccoli Sample; 6. Clean water